Gender wage gap in European emerging markets: A meta-analytic perspective - Ichiro Iwasaki; Mihoko Satogami (Journal for Labour Market Research, 2023)
In this paper, we report the results of a meta-analysis of 670 estimates extracted from 53 previous research works to estimate the gender wage gap in European emerging markets. A meta-synthesis of collected estimates exhibits that the gender differences have a statistically significant and economically meaningful impact on wage levels. Synthesis results also reveal that the gender wage gap in countries with EU membership is lower than that in non-EU member states and, nevertheless, the wage gap between men and women has a tendency to diminish over time in the region as a whole. The meta-regression analysis of literature heterogeneity and test for publication selection bias back up the findings obtained from the meta-synthesis.
Keywords: D31; I26; J31; P23; P36; 330; Gender wage gap; Research synthesis; Meta-regression analysis; Publication selection bias; European emerging markets